Diagnosis of inflammatory bowel disease according to human IgG4 and possibilities of evaluating efficacy of the therapy - Stepanov, Y. M.; Tarasova, T. S.; Stoikevych, M. V.; Gaydar, Y. A.; MylostуvaD. F.; TatarchukО. M.; Petishko, O. P. (Regulatory Mechanisms in Biosystems, 2022)
Taking into account the progress of understanding diagnosis, course prognosis, evaluation of effectiveness of therapy of inflammatory bowel disease and also differentiation diagnosis between its main forms – ulcerative colitis and Crohn’s disease, the search for efficient non-invasive markers for solving those issues is extremely relevant. The patients were divided into groups depending on nosology and severity of the course of the disease. All the patients had undergone endoscopic study for diagnosis verification and biopsy samples were taken for further detection of tissue IgG4 using the immunohistochemical method. Also, we determined concentration of serum IgG4. Increase in IgG4content in blood serum was determined in 54.0% of the cases of inflammatory bowel disease. Concentration of IgG4 in patients suffering ulcerative colitis was higher (by 2.31 and 2.46 times) compared with its level in the control group and patients with Crohn’s disease, respectively. We found relationships between the concentration of serum IgG4 and the activity of the disease. In patients with ulcerative colitis, increased tissue IgG4 was found more often than in patients with Crohn’s disease (by 2.77 times, Р < 0.05). We determined the relationship between tissue IgG4 and histological activity. Simultaneous increase in serum IgG4 and presence of tissue IgG4 during ulcerative colitis were more frequent than during Crohn’s disease (by 2.66 times). In all examined groups of patients, we determined decrease in serum IgG4 content (by 1.66 times) after treatment. Concentration of serum IgG4 and positive tissue IgG4 in ulcerative colitis patients exceeded such in Crohn’s disease patients, which may be used for differentiation diagnosis between those disease types. We determined dependence of IgG4 concentration on severity and duration of the disease, which could be used as a prognostic marker. Decrease in IgG4 content in blood serum against the background of the therapy shows that this indicator could be used as a marker of treatment efficacy. Perspectives of further studies are as follows: parameters of concentration of serum IgG4 and presence of tissue IgG4 could be used as diagnostic and prognostic biomarkers and be introduced to practice for differentiation diagnosis between ulcerative colitis and Crohn’s disease, and could be used as prognostic marker of severity of the disease and therapy efficacy.